Evidence of High-latitude Emission in the Prompt Phase of GRBs: How Far from the Central Engine are the GRBs Produced? - Z. Lucas Uhm; Donggeun Tak; Bing Zhang; Judith Racusin; Daniel Kocevski; Sylvain Guiriec; Bin-Bin Zhang; Julie McEnery (The Astrophysical Journal Letters, 2024)
One of the difficulties in nailing down the physical mechanism of gamma-ray bursts (GRBs) comes from the fact that there has been no clear observational evidence on how far from the central engine the prompt gamma rays of GRBs are emitted. Here we present a simple study addressing this question by making use of the “high-latitude emission” (HLE). We show that our detailed numerical modeling exhibits a clear signature of HLE in the decaying phase of “broad pulses” of GRBs. We show that the HLE can emerge as a prominent spectral break in F _ν spectra and dominate the peak of ν F _ν spectra even while the “line-of-sight emission” (LoSE) is still ongoing. This finding provides a new view of HLE emergence since it has been believed so far that the HLE can show up and dominate the spectra only after the LoSE is turned off. We remark, however, that this “HLE break” can be hidden in some broad pulses, depending on the proximity between the peak energies of the LoSE and the HLE. Therefore, this new picture of HLE emergence explains both the detection and nondetection of HLE signature in observations of broad pulses. Also, we present three examples of Fermi Gamma-ray Burst Monitor GRBs with broad pulses that exhibit the HLE signature. We show that their gamma-ray-emitting region should be located at ∼10 ^16 cm from the central engine, which places a constraint on the GRB models.